Estudo longitudinal das dimensões do déficit de atenção, hiperatividade/impulsividade e comportamento antissocial na infância e traços de personalidade na idade adulta - Luciana Sampaio Braga (2017)
The present study aimed to investigate the association between externalizing behaviors in childhood and personality traits in adulthood from a prospective longitudinal design. Personality was definedfrom the model of the five major personality factors, Big Five. In 2002, when the "Longitudinal Study of the Psychological Competences of Schoolar Children" began, the sample included 620 students, children and adolescents, from the Centro Pedagógico of Universidade Federal de Minas Gerais (UFMG) who were evaluated in measures of the externalizing behaviors (Deficit of Attention, Hyperactivity / Impulsiveness and Antisocial Behavior) by teachers through the ADHD scale - teachers version. In 2015/2016, these participants were invited to undertake the second stage of the study. A total of 104 subjects (M = 23.31 years; SD = 2.18) were evaluated, 67 (66.3%) males, through the personality scale NEO-PI-R. The results show significant correlations and moderatemagnitudes between the externalizing behaviors and Consciousness and Agreeblaness. The attention deficit was negatively correlated to the Conscientiousness trait (r = -0.234, p <0.018). The Agrebleness trait correlated negatively to the three dimensions of externalizing behaviors: attention deficit (r = -2.78, p <0.01), hyperactivity / impulsivity (r = -0.286, p <0.04) and antisocial behavior (r = -0.229, p <0.021). For the externalizing behaviors, significant differences were found for males in the dimensions of Attention Deficit (H = 7.98, p <0.05) and hyperactivity / impulsivity (H = 6.103, p <0.013). For personality, the female gender presented a significant difference in the Neuroticism factor (t = 2,921, p <0.002). There were no significant associations between externalizing behaviors in childhood and use of licit or illicit substances in adulthood. In general, the results point to a relationship between patterns of behavior in childhood and personality traits in adulthood